Pengungkapan Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderating - Ida Nuryana; Elisabet Bhebhe (Postgraduate Program Merdeka University, 2019)
The purpose of this study was to determine the effect of corporate social responsibility disclosure on firm value with profitability as a moderating variable. The sample used in the study was 90 observations from the basic industrial and chemical manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. The data in the study came from the secondary data obtained through technical documentation. The data of this study was to qualify the classical assumption and moderated regression analysis (MRA) test requirements. the results of the analysis show that the corporate social responsibility disclosure does not affect the company value and profitability can moderate the relationship between corporate social responsibility disclosure and company value. DOI: https://doi.org/10.26905/afr.v2i2.3261